The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.2134/agronj2002.1317
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Light Environment and Yield of Narrow‐Row Cotton as Affected by Canopy Architecture

Abstract: Alterations of plant architecture in narrow‐row cotton (Gossypium hirsutum L.) using management and genetic strategies to improve light penetration into the canopy may increase crop yields. The objective of this study was to quantify how plant architecture changes affect light penetration into the canopy, yield, and yield components of narrow‐row cotton. The study was conducted on a Glendale clay loam soil (fine montmorillonitic, thermic Typic Torrert). Two field experiments were established on 0.76‐m rows in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…This phenomenon may result from tight competition of plants for water, light, and nutrient under high plant density, thus increasing the amount of proline. Reta-Sanches and Fowler (2002) suggested that changing plant densities and increasing light penetration in lower parts of the canopy can improve plant yield. In the present study, seed yield decreased with increasing plant densities (60 plants m -2 ) for all canola cultivars, which possibly resulted from reduction of light penetration under high plant densities.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon may result from tight competition of plants for water, light, and nutrient under high plant density, thus increasing the amount of proline. Reta-Sanches and Fowler (2002) suggested that changing plant densities and increasing light penetration in lower parts of the canopy can improve plant yield. In the present study, seed yield decreased with increasing plant densities (60 plants m -2 ) for all canola cultivars, which possibly resulted from reduction of light penetration under high plant densities.…”
Section: Discussionmentioning
confidence: 99%
“…(1997) reported that planting density did not affect the leaf area in tomato. While increasing the plant populations per unit area, intra-plant competition becomes more important and light interception also varied with crop development; the planting pattern optimises the available natural and unnatural resources and row spacing become important in crop canopy structure (Andrade et al, 2002;Reta-Sanchez and Fowler, 2002;Sharratt and McWilliams, 2005). The state of development of the plant determines the pattern distribution of dry matter in different organs of the plant, and the leaf area growth determines the light interception pattern (Heuvelink and Marcelis, 1989).…”
Section: Resuls and Discussionmentioning
confidence: 99%
“…The economic yield of cotton is basically influenced by the balance of assimilate allocation between vegetative and reproductive organs (Reta-Sánchez and Fowler, 2002;Jones et al, 1996;Kerby et al, 1993). In China, intensive farming technologies involving plastic mulching, plant topping and pruning have been widely adopted for cotton production in the last 40 years (Dai and Dong, 2014).…”
Section: Introductionmentioning
confidence: 99%